Digitalisation, data-driven dynamic capabilities and responsible innovation: An empirical study of SMEs in China - Chen, Yantai; Li, Jing; Zhang, Jingwen (Asia Pacific journal of management, 2024)
Research on responsible innovation (RI) is essential and effective for developed countries to achieve sustainable development goals; however, RI is still relatively undiscussed in the emerging Asia–Pacific markets. With the rapid development of big data-related technologies and their application, digital platforms have become a dominant organisational form in the current industrial practice; SMEs have had to conduct digital transformation and realise value creation by embedding the platform ecosystem. However, this has given rise to irresponsible innovation practices. Few studies have investigated the implementation or realisation of RI in emerging market platforms. As the core of RI for the SMEs embedded in the platform is the ecosystem view, which contemplates multiple actors engaging in value co-creation, different from a single actor in existing studies, the sustainable development performance of SMEs is one of the best evidence of the overall RI realisation of the whole platform ecosystem. On the basis of these discussions, we construct a core theoretical model and combine it with existing literature and theories, mainly with RI, dynamic capabilities theory, and neo-institutional theory. We empirically analyse 268 Chinese SMEs embedded in the platform. The results reveal that the data-driven dynamic capabilities of SMEs can become the key driving force in improving their sustainable development performance, thus guiding the platform enterprises’ RI quality. In addition, digital regulatory pressure and digital customer pressure exert a significant positive moderating effect on the association between RI quality and sustainable development performance, which may be closely related to the infantile stage of SMEs’ digital transformation in emerging Asia–Pacific markets.